Basal insulin therapy: Unmet medical needs in Asia and the new insulin glargine in diabetes treatment - Tien, Kai‐Jen (J Diabetes Investig, 2019)
Diabetes remains a global epidemic and a tremendous health challenge, especially in the Asian population. Dramatic increases in the prevalence of diabetes across different countries or areas in Asia have been reported in recent epidemiological studies. Although clinical guidelines have strengthened appropriate antihyperglycemic medications and lifestyle modifications for optimal diabetes management, inadequate glycemic control still occurs in many patients with an increased risk of developing microvascular and macrovascular complications. Insulin administration is the main therapy for diabetes in response to the inability to secrete insulin, and is recommended in current guidelines to treat patients with type 2 diabetes after failure of oral antidiabetic drugs. Clinical studies have shown that long‐acting insulin analogs improve basal glycemic control with reduced risk of hypoglycemia. In the present review, we discuss previous challenges with basal insulin therapy in Asia, the pharmacological development of insulin analogs to overcome the unmet medical needs and recent clinical studies of the new ultra‐long‐acting insulin analog, insulin glargine U300. Furthermore, relevant findings of current real‐world evidence are also included for the comparison of the efficacy and safety of different insulin formulations. Based on the accumulating evidence showing a low incidence of hypoglycemia and technical benefits of dose titration, treatment with glargine U300 can be a promising strategy for Asian diabetes patients to achieve glycemic targets with favorable safety.